Capital Structure and Dividend Policy Role in Building Stock Price - Luluk Muhimatul Ifada; Sri Sulistyowati; Maya Indriastuti (Universitas Pendidikan Indonesia, 2021)
This research aims to determine the effect of capital structure variables on stock price through dividend policy. Stock price is important because it can be used to assess the condition of a company and it becomes a reference for investors to invest in the company. The populations of this research were all manufacturing companies listed on Indonesia Stock Exchange for the period of 2016-2020. The sampling technique used purposive sampling method so that 230 manufacturing companies were obtained. All data were processed using Structural Equation Modeling analysis based on Partial Least Square. The results of this research indicated that the capital structure has a positive effect on dividend policy. In addition, capital structure and dividend policy have a positive effect on stock price. Alternatively stated, dividend policy succeeded in mediating the effect of capital structure on stock price.